2009
DOI: 10.1016/j.freeradbiomed.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi infection disturbs mitochondrial membrane potential and ROS production rate in cardiomyocytes

Abstract: In this study, we investigated the role of Trypanosoma cruzi invasion and inflammatory processes in reactive oxygen species (ROS) production in mouse atrial cardiomyocyte line (HL-1) and primary adult rat ventricular cardiomyocytes. Cardiomyocytes were incubated with T. cruzi (Tc) trypomastigotes, Tc lysate (TcTL) or Tc secreted proteins (TcSP) for 0-72 h, and ROS measured by amplex red assay. Cardiomyocytes infected by T. cruzi (but not those incubated with TcTL or TcSP) exhibited a linear increase in ROS pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 41 publications
9
101
0
1
Order By: Relevance
“…This study suggested that Ca 2ϩ uptake and mitochondrial ROS production might be the early signaling events in the activation of PARP-1. 109 Recent studies 115 in an in vitro model of cardiomyocyte infection by T. cruzi support the previously described notion because we found that invasion by parasites triggered MPT and loss of membrane potential, which resulted in an inefficiency of the electron transport chain and increased ROS production. The ROS-induced DNA damage elicited PARP-1 activation; the latter, in turn, led to an increased formation of PARs.…”
Section: Parp-1-related Signaling Pathwayssupporting
confidence: 88%
“…This study suggested that Ca 2ϩ uptake and mitochondrial ROS production might be the early signaling events in the activation of PARP-1. 109 Recent studies 115 in an in vitro model of cardiomyocyte infection by T. cruzi support the previously described notion because we found that invasion by parasites triggered MPT and loss of membrane potential, which resulted in an inefficiency of the electron transport chain and increased ROS production. The ROS-induced DNA damage elicited PARP-1 activation; the latter, in turn, led to an increased formation of PARs.…”
Section: Parp-1-related Signaling Pathwayssupporting
confidence: 88%
“…Finally, the infectivity of TcAPx-CcP overexpressers was evaluated in cardiomyocytes, cells where amastigotes can reside during chronic infection. It has been shown that T. cruzi cardiomyocyte infection leads to the establishment of host-mitochondrial dysfunction, with an increase in H 2 O 2 and inflammatory cytokine (IL-1β and TNF-α) production (39). We evaluated the infectivity of TcAPx-CcP overexpressers following 96 h of infection, an incubation time sufficient to cause mitochondrial dysfunction in cardiomyocytes and to achieve amastigote replication in the host cell cytoplasm.…”
Section: Enhanced Virulence Of Tcapx-ccp Overexpressers In Cellular Amentioning
confidence: 99%
“…Trypanosoma cruzi, the causative agent of Chagas disease, infects cardiomyocytes, alters their mitochondrial potential, and induces ROS (1). This overwhelms the antioxidant defenses and produces persistent oxidative stress (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%